Morse potential energy spectra through the variational method and supersymmetry - Filho, Elso Drigo [UNESP]; Ricotta, Regina Maria [UNESP] (Elsevier, 2000)
The Variational Method is applied within the context of Supersymmetric Quantum Mechanics to provide information about the energy and eigenfunction of the lowest levels of a Hamiltonian. The approach is illustrated by the case of the Morse potential applied to several diatomic molecules and the results are compared with stabilished results. (C) 2000 Elsevier Science B.V.
Keywords: atomic particle; dissociation; energy; mathematical analysis; molecule; oscillator; quantum mechanics